Immunotherapy with IgY Antibodies toward Outer Membrane Protein F Protects Burned Mice against Pseudomonas aeruginosa Infection - Fatemeh Norouzi; Bahador Behrouz; Mahya Ranjbar; Seyed Latif Mousavi Gargari (Journal of Immunology Research)
Burn patients with multidrug-resistant Pseudomonas aeruginosa infections commonly suffer from high morbidity and mortality, which present a major challenge to healthcare systems throughout the world. Outer membrane protein F (OprF), as a main outer membrane porin, is required for full virulence expression of P. aeruginosa. The aim of this study was to evaluate the protective efficacy of egg yolk-specific antibody (IgY) raised against recombinant OprF (r-OprF) protein in a murine burn model of infection. The hens were immunized with r-OprF, and anti-r-OprF IgY was purified using salt precipitation. Groups of mice were injected with different regimens of anti-OprF IgY or control IgY (C-IgY). Infections were caused by subcutaneous injection of P. aeruginosa strain PAO1 at the burn site. Mice were monitored for mortality for 5 days. The functional activity of anti-OprF IgY was determined by in vitro invasion assays. Immunotherapy with anti-OprF IgY resulted in a significant improvement in the survival of mice infected by P. aeruginosa from 25% to 87.5% compared with the C-IgY and PBS. The anti-OprF IgY decreased the invasion of P. aeruginosa PAO1 into the A549. Passive immunization with anti-OprF IgY led to an efficacious protection against P. aeruginosa burn infection in the burn model.